Maize (Zea mays L.) nutrient use efficiency as affected by formulated fertilizer with clinoptilolite zeolite - Lija, Magdalina; Haruna, Ahmed Osumanu; Kasim, Susilawati (College of Food and Agriculture, United Arab Emirates University, 2014)
Excessive uses of fertilizer can create environmental problems such as soil pollution. This problem could be reduced by amending clinoptilolite zeolite with compound fertilizers. The objective of this study was to evaluate the effect of clinoptilolite zeolite rates in compound fertilizers (N: P: K) on maize nutrients uptake and use efficiency. The following treatments were considered and evaluated: soil alone (T1), 44.6 g 5:3:2 formulated fertilizer (12.83 g compound fertilizer + 31.77 g zeolite) (T2), 44.6 g 5:5:5 formulated fertilizer(18.24 g compound fertilizer + 26.36 g zeolite) (T3), 37.17 g 6:6:6 formulated fertilizer (18.25 g compound fertilizer + 18.92 g zeolite) (T4), 22.30 g 10:10:10 formulated fertilizer (18.24 g compound fertilizer + 4.06 g zeolite) (T5), and 14.87 g 15:15:15 commercial fertilizer (T6). Selected soil chemical properties, as well as, dry weight, nutrients concentrations, uptake and use efficiency were measured. Compound fertilizers with zeolite increased soil pH compared to soil alone (T1) and commercial fertilizer (T6). Application of compound fertilizer did no significantly affect total N and available nitrate in the soil. T6 gave better plant height and dry matter production among treatments. Nitrogen concentrations for all plant parts were similar for all treatments. T6 showed better P concentrations, uptake, and use efficiency. K concentrations in maize plant parts were significantly increased for treatments with zeolite except for roots. T5 and T6 significantly increased K uptake. T6 significantly increased N and P uptake and use efficiency, while T2 significantly increased K use efficiency. Amending N, P, and K fertilizers with higher dosage of clinoptilolite zeolite improved soil chemical properties, nutrient uptake of Masmadu variety. Compound fertilizers amended with clinoptilolite zeolite enhanced K use efficiency of Masmadu maize variety.